A functional design and synthesization for electrocatalytic hydrogen evolution material on MoS2/Co3S4 hybrid hollow nanostructure. (10th April 2018) - Lei, Xiang; Yu, Ke; Li, Honglin; Zhu, Ziqiang
Abstract: A central challenge in large scale sustainable hydrogen production by electrolyzing water is to develop efficient and economical electocatalysts with nanostructural materials. This work herein reports the facile solvothermal synthesis of MoS2 /Co3 S4 hollow nanostructural co-catalyst with high activity and stability for electrochemical hydrogen evolution reaction (HER) by compositing cheap and HER-active MoS2 on Co3 S4 HER catalyst. By morphology and structure modulations, this high-quality nanostructure, which is confirmed by several characterizing techniques, can be considered as excellent catalyst to split water into H2 in a wide pH range via the electric drive. Corresponding electrochemical measurement results of 55.6 mV dec −1 and 115.3 mV dec −1 Tafel slope in acid (pH = 0.3) and alkaline (pH = 14) media demonstrates our predictions. We believe that such performance improvement is mainly due to the much increased active sites for catalysis because of composition process and hollow structure. These findings open up an effective and propagable strategy for nanostructural HER catalysts synthesis. Graphical abstract: Highlights: MoS2 /Co3 S4 hollow polyhedra is fabricated via solvothermal method. MoS2 /Co3 S4 hollow polyhedra exhibits pH-universal catalytic activity for HER. The enhanced mechanism can be attributed to the synergistic effect of MoS2 and Co3 S4 .